Development of the AI-Based Edugame 'Si Robot Pintar' in Enhancing Cognitive Abilities and Character Development of Early Childhood Children in Islamic Boarding Schools - Rihlah, Jauhara; Rulyansah, Afib; Hardiningrum, Andini; Savira (Journal of Applied Science, Engineering, Technology, and Education, 2026)
This study aims to develop the Si Robot Pintar Edugame, an AI-based interactive tool designed to enhance Cognitive Abilities and Character Development in early childhood at Pondok Pesantren. The product development followed the Research and Development (R&D) model, adopting the ADDIE framework (Analysis, Design, Development, Implementation, Evaluation) to create a technology-driven, engaging learning environment that fosters both cognitive and moral growth. A quasi-experimental design was employed in this study with three groups: two experimental groups (one using the Si Robot Pintar Edugame and the other using interactive videos) and a control group (using worksheets). Pretest and posttest measures were used to assess improvements in cognitive skills and character development. The results revealed that the Si Robot Pintar Edugame had the greatest effect, with the experimental group showing a 40% increase in posttest scores, compared to a 15% improvement in the control group. The Si Robot Pintar Edugame group exhibited the largest effect size (0.890), followed by the interactive video group (0.875), and the control group (0.540), underscoring the superiority of this AI-based intervention. The Si Robot Pintar Edugame significantly enhanced children’s abilities in identifying emotions and controlling emotions, which are vital aspects of emotional regulation and self-regulation. The game was especially effective in promoting cognitive skills and fostering character traits such as self-discipline, empathy, and critical thinking, all of which align with the educational objectives of Pondok Pesantren and Islamic teachings. These findings suggest that integrating AI and interactive tools in Islamic educational settings can substantially improve Cognitive Abilities and Character Development in children. The study concludes that the Si Robot Pintar Edugame is an effective, innovative educational tool that plays a significant role in enhancing both cognitive and moral development in early childhood at Pondok Pesantren.